Obesity is linked to disease severity in moderate to severe atopic dermatitis: data from the prospective observational TREATgermany registry - Traidl, Stephan; Hollstein, Moritz Maximilian; Kroeger, Nadine; Fischer, Sascha; Heratizadeh, Annice; Heinrichmeyer, Luise; Kind, Barbara; Siegels, Doreen; Abraham, Susanne; Schäfer, Thomas; Augustin, Matthias; Harder, Inken; et al. (Journal of the European Academy of Dermatology and Venereology, 2025)
Background There are conflicting data on a potential association between obesity and atopic dermatitis (AD). The purpose of this study was to investigate the relationship between obesity and AD disease severity. Methods Patients from the TREATgermany registry cohort were divided into three groups according to their body mass index (BMI). Due to low numbers, underweight patients (BMI <18.5 kg/m2) were excluded from the analysis. Physician- and patient-reported disease severity scores as well as additional phenotypic characteristics were evaluated for association with BMI. Generalized linear mixed models and multinomial logit models, respectively, were applied to investigate the association of BMI, age, sex and current systemic AD treatment with disease severity. Results This study encompassed 1416 patients, of which 234 (16.5%) were obese (BMI ≥30 kg/m2). Obesity was associated with lower educational background and smoking. Otherwise, obese and non-obese AD patients had similar baseline characteristics. Increased BMI was associated with higher oSCORAD (adjusted β: 1.24, 95% CI: 1.05-1.46, p = 0.013) and Patient-oriented eczema measure (POEM) (adjusted β: 1.09, 95% CI: 1.01-1.17, p = 0.038). However, the absolute difference in the overall oSCORAD was small between obese and non-obese AD patients (Δ oSCORAD = 2.5). Allergic comorbidity was comparable between all three groups, with the exception of asthma which was more pronounced in obese patients (p < 0.001). Discussion In this large and well-characterized AD patient cohort, obesity is significantly associated with physician- and patient-assessed measures of AD disease severity. However, the corresponding effect sizes were low and of questionable clinical relevance. The overall prevalence of obesity among the German AD patients was lower than in studies on other AD cohorts from different countries, which confirms previous research on the German population and suggests regional differences in the interdependence of AD and obesity prevalence.